2023
DOI: 10.1002/ange.202210209
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Against Amyloid: Dimeric Amyloid Fragment Ameliorates Cognitive Impairments by Direct Clearance of Oligomers and Plaques

Abstract: Amyloid-β (Aβ) in the form of neurotoxic aggregates is regarded as the main pathological initiator and key therapeutic target of Alzheimer's disease. However, anti-Aβ drug development has been impeded by the lack of a target needed for structure-based drug design and low permeability of the blood-brain barrier (BBB). An attractive therapeutic strategy is the development of amyloid-based anti-Aβ peptidomimetics that exploit the self-assembling nature of Aβ and penetrate the BBB. Herein, we designed a dimeric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(150 reference statements)
0
0
0
Order By: Relevance
“…For instance, it has been reported that the accumulation of amyloid plaque in the brain can be ameliorated by delivering amyloid beta (1−17) dimers to suppress the progress of Alzheimer's disease. 82 Employing engineered cells to produce the peptide, cell therapeutics could potentially be utilized in the treatment of neurological disorders in such a fashion.…”
Section: Modulation Of Neuronal Microenvironmentsmentioning
confidence: 99%
“…For instance, it has been reported that the accumulation of amyloid plaque in the brain can be ameliorated by delivering amyloid beta (1−17) dimers to suppress the progress of Alzheimer's disease. 82 Employing engineered cells to produce the peptide, cell therapeutics could potentially be utilized in the treatment of neurological disorders in such a fashion.…”
Section: Modulation Of Neuronal Microenvironmentsmentioning
confidence: 99%